2021
DOI: 10.3390/molecules26216647
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Studies on the Nephroprotective Potential of Celastrus paniculatus against Lead-Acetate-Induced Nephrotoxicity in Experimental Rats: Role of the PI3K/AKT Signaling Pathway

Abstract: Chemicals can induce nephrotoxicity, with damage to different segments of the nephron and deterioration of renal function. Nephrotoxicity due to exposure to a toxin such as carbon tetrachloride, sodium oxalate, or heavy metals is the most common cause of kidney injury. The current study aimed to evaluate the protective effects of Celastrus paniculatus seed extract against lead-acetate-induced nephrotoxicity by evaluating the histopathology, immunohistochemistry, ultrastructure, and phosphoinositide 3-kinase (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…In the present study, MPP + treatment reduced the expression levels of p-GSK-3β (Ser9). Moreover, this result was consistent with previous evidence that CPSE treatment inhibits the occurrence of lead acetate-induced degenerative changes in the renal tubules with significantly increased PI3K and AKT mRNA expression levels in CP-treated rats (19) This previous finding indicated that CPSE may inhibit lead acetate-induced detrimental changes in the kidneys by regulating the PI3K/AKT signaling pathway (19). Since the phosphorylation status of GSK-3β is primarily regulated by AKT, and various stimulating factors activate the PI3K/AKT pathway (5), the present study suggested that CPSE inhibited the MPP + -induced model of PD in SH-SY5Y cells by regulating PI3K/AKT/GSK-3β signaling.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, MPP + treatment reduced the expression levels of p-GSK-3β (Ser9). Moreover, this result was consistent with previous evidence that CPSE treatment inhibits the occurrence of lead acetate-induced degenerative changes in the renal tubules with significantly increased PI3K and AKT mRNA expression levels in CP-treated rats (19) This previous finding indicated that CPSE may inhibit lead acetate-induced detrimental changes in the kidneys by regulating the PI3K/AKT signaling pathway (19). Since the phosphorylation status of GSK-3β is primarily regulated by AKT, and various stimulating factors activate the PI3K/AKT pathway (5), the present study suggested that CPSE inhibited the MPP + -induced model of PD in SH-SY5Y cells by regulating PI3K/AKT/GSK-3β signaling.…”
Section: Discussionsupporting
confidence: 93%
“…This work revealed marked increase in the amount of collagen fibers distribution in the renal sections stained by Masson Trichome in group (II). Similarly, Balaji et al (29) documented that the kidneys' entire collagen content significantly increased in lead acetatetreated rats compared with control rats. But conversely, the renal sections from chrysin treated group and zinc treated group showed moderate increase in the density and distribution of collagen fibers.…”
Section: Discussionmentioning
confidence: 86%
“…The kidney is a vulnerable vital organ in drug elimination; therefore, chemical exposure to drugs and their metabolites will jeopardize the urinary tract system [ 18 , 19 ]. Toxic damage (either acute or chronic) to the kidney is attributed to various substances, such as hydrocarbons, heavy metals, and proven nephrotoxic drugs, as well as aflatoxins that might result in renal cancer or failure [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%